Study of the Number of Rings in Carbon Nano Structures (Fullerenes and Nanotubes) - (ARMAN) TAHERPOUR†, AVAT (Asian Journal of Chemistry, 2024)
One of the questions is determining the number of rings in fullerenes and nanotubes. Here, for solving this problem, a simple, fast and high accuracy method is explained. Application of this method has shown good results. Determining the number of rings (NR) in carbon nanostructures such as fullerenes, nanotubes (SWNT) and other nanocarbon structures is the main aim of this study. This structural index that is based on the degrees of unsaturation may useful in the QSAR and QSPR studies concern to the carbon nanostructures.